OPTIMIZING STUDENT REASONING THROUGH READING LITERACY WITH THE DEVELOPMENT OF E-LKPD IN THE TOURISM CONTEXT - Oktarina, Detia Aulia; Alwi, Zahra; Saripudin, Agus (University of Kuningan, 2024)
This research aims to develop and evaluate the practicality of interactive Electronic Student Worksheet (E-LKPD) to support increasing students' reasoning competence toward reading literacy in a tourism context via the Blogspot platform. This research is development research that combines qualitative and quantitative approaches. The method used is the Jolly and Bolitho development method. Steps taken include the following: (1) identifying material needs, (2) exploring needs, (3) contextual realization, (4) pedagogical realization, (5) material products, and (6) evaluating material according to objectives. This research involved Indonesian language teachers and 62 seventh-grade students at SMPN 20 Palembang as the research subjects. Data collection methods use interviews, questionnaires, and tests. Qualitative data analysis uses a descriptive approach, while qualitative data is analyzed using Likert scale calculations. The results of distributing the needs analysis questionnaire to students indicated that 60.32% strongly agreed, while 33.44% agreed to develop E-LKPD. Product validation was carried out by three validators, namely content validators, content suitability, and language, with a total validation value of 86.67% (very valid). The product feasibility test scored 89.16% (very practical) in the small group test. The effectiveness test for E-LKPD relied on pretest results, which averaged 61.42, and posttest results, averaging 74.85. There was a significant increase in the 2-tailed results (0.000<0.5). The results indicate that the developed E-LKPD can enhance students' reading literacy skills.